Strength of porous concrete pavement at different curing methods - Mohd. Yusak, Mohd. Ibrahim (Penerbit UTM Press, 2015)
Porous concrete pavement has been used in some countries as a solution to environmental problems. Contrary to conventional concrete pavement, there is still lack of knowledge in some areas of production and performance of porous concrete pavement. One of the issue concern is curing conditions. These greatly affect the performance of porous concrete pavement. This paper elaborates the experimental results examining the influence of curing method and makes a comparison between five different curing methods on the strength of porous concrete pavement specimens. The properties analyzed include compressive strength, tensile splitting strength and flexural strength. The experimental results indicate that the different curing methods give a different effect to concrete strength. Based on the results obtained in this experiment, curing method by using polyethylene bag promise a good result and better performance to porous concrete pavement specimen strength.